2004
DOI: 10.1017/s002185960500482x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of di-nitrogen fixation by pea to the productivity and N budget of a wheat-based cropping system

Abstract: SU MMARYThe productivity and N budget of three crop rotations were determined in a field study beginning in 1997. A duplicate experiment was initiated in 1998; each experiment lasted 3 years. The rotations were : continuous wheat (WWW), oilseed rape-wheat-wheat (RWW) and pea-wheat-wheat (PWW). Wheat and oilseed rape received 0 or 60 kg N/ha, apart from fertilized wheat following pea, which received 22 . 5 kg N/ha, and in the third year of the rotation all plots received 60 kg N/ha. Peak N 2 fixation by pea ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Published data used to calculate N inc were limited to Northern Great Plains research in which both grain yield and N 2 fixation values were reported as a minimum requirement (Table 1). In most instances, estimates of N 2 fixation were determined using 15 N enriched or natural abundance methods, although a limited number of studies used a difference method [i.e., a comparison of the N uptake in the fixing crop to a nonfixing reference crop, e.g., Soon and Arshad (2004)] to estimate N 2 fixation.…”
Section: Methodsmentioning
confidence: 99%
“…Published data used to calculate N inc were limited to Northern Great Plains research in which both grain yield and N 2 fixation values were reported as a minimum requirement (Table 1). In most instances, estimates of N 2 fixation were determined using 15 N enriched or natural abundance methods, although a limited number of studies used a difference method [i.e., a comparison of the N uptake in the fixing crop to a nonfixing reference crop, e.g., Soon and Arshad (2004)] to estimate N 2 fixation.…”
Section: Methodsmentioning
confidence: 99%
“…Variation in the amount of N fixed by various pulse species has been reported by different groups in the past. Jensen et al (2010) reported 83 kg ha −1 biological nitrogen fixation by pea, while the quantity was 61 kg ha −1 according to Soon and Arshad (2004). In the study of Jensen et al (2010), biological nitrogen fixation by chickpea, lentil, and faba bean was 54, 50, and 135 kg ha −1 , respectively, while Peoples et al (2009) showed that biological nitrogen fixation by chickpea, pea, and faba bean was 54, 83, and 118 kg ha −1 , respectively.…”
Section: Nitrogen Fixationmentioning
confidence: 96%
“…After reviewing the literature, Walley et al (2007) reported that the median value of total plant N derived from the atmosphere was 88% for faba bean, 60% for lentil, and 55% for field pea crops grown in the northern Great Plains region of North America. Little or no N fertilizer is required during their growth phase, and subsequent crops are able to access greater soil mineral N thereby increasing yields and (or) reducing fertilizer N requirements (Soon and Arshad 2004;Tanaka et al 2007). Largely due to reduced fertilizer N inputs, N 2 O emissions during the pulse phase of cropping sequences appear to have substantively lower N 2 O emissions compared with the fertilized phases of the cropping system (Lemke et al 2007;Dusenbury et al 2008;Jeuffroy et al 2013).…”
Section: Introductionmentioning
confidence: 99%